KORELASIPERSEPSISISWATENTANGKEMAMPUANMENGAJAR GURUDENGANHASILBELAJAR SOSIOLOGISISWAKELASXI - Graevina Aulelia Oroh; Amrazi Zakso; Rustiyarso Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractTheresearchtitleis"CorrelationofStudents'PerceptionsofTeacher TeachingAbilitywithSociologyLearningOutcomesofClassXIStudentsof SMANegeri1SungaiRaya,KubuRayaRegency".Thedescriptiveresearch methodusesaquantitativeapproach.Theresultsofthestudywereas follows:1)Students 'perceptions ofteachers who taughtsociology subjects,based on the results ofthe research conducted,students' perceptionsofsociologyteacherswhotaughtsociologysubjects,inthis casewereverygood.2)CorrelationofStudentPerceptionsaboutthe teachingabilityofteacherssignificantlyinfluencetheSociologyLearning OutcomesofClassXIStudentsofSMANegeri1SungaiRaya,KubuRaya Regency.3)How closelyisthecorrelationbetweentheCorrelationof Students'PerceptionsofTeacherTeachingAbilitywithSociologyLearning OutcomesofClassXIStudentsofSMANegeri1SungaiRaya,KubuRaya Regency.Obtainedt-valueof8,370withasignificancevalue(Sig.)Of0,000. Thevalueoftcount(8.370)>ttable(1.701),itcanbestatedthatthe hypothesistestHoisrejectedandHaisaccepted,whichmeansthatthe Correlation ofStudentPerceptions ofTeacherTeaching Ability and SociologyLearningOutcomesofClassXIStudentsofSMANegeri1Sungai Raya,KubuRayaRegency.Keyword:CorrelationofStudentPerceptionsandAchievement Motivation,StudentSociologyLearningOutcomes.